Lessons in leadership - Adubato, Steve (Rutgers University Press, 2016)
In this practical guide, Emmy Award-winning public broadcasting anchor Steve Adubato teaches readers to be self-aware, empathetic, and more effective leaders at work and at home. With Lessons in Leadership, readers can learn to lead others through difficult economic times, to mentor rising leaders, to provide straight talk to underperforming employees, and even how to lead a company through a significant change.